TISA/TTIP/TPP and the Exclusion of the BRICS: The possibles impacts in Brazil - Nascimento, Dmitri Felix (2018)
The negotiations during the World Trade Organization rounds have called into question the lack of consensus on the liberalization/regulation of trade in various sectors –agriculture, automotive, semi-manufactured goods and services— that directly affect the developing countries. The de-veloped countries have strengthened their positions giving priority to agreements in the service sector with Trade in Services Agreement (TISA) which comprises the areas of telecommunica-tions, e-commerce, air and maritime transport, biotechnology, movement of natural persons, na-tional regulations and postal services. As a strategic sector, it constitutes nearly 80% of the US and UE economies. The negotiations around TISA, Transatlantic Trade and Investment Partner-ship (TTIP) and Trans-Pacific Partnership (TPP) occurred behind closed doors as parallel negotia-tions under the leadership of the United States and European Union. With the collaboration of other 23 countries, according to documents obtained by WikiLeaks, they excluded the BRICS countries and others. Arising instability and lack of legitimacy among multilateral agencies after the financial and economic crisis of 2008, call into question the entities created after the Bretton Woods Conferences. This study aims to identify the consequences that these agreements will bring in the field of international trade in relation to the BRICS countries, and specifically about Brazil.